DIGITAL TRANSFORMATION: IS THERE ANY LINK WITH MARKET PERFORMANCE OF PHARMACEUTICAL MICRO, SMALL AND MEDIUM-SIZED ENTERPRISES IN KENYA - Githua, Martha Njeri; Muathe, Stephen Makau (American International Journal of Social Science Research, 2024)
The business-operating environment in Kenya and especially in the City County of Nairobi has caused a large number of pharmaceutical Micro, Small, and Medium-Sized Enterprises report profit warnings and thus experience performance issues. Data from the World Bank for the previous two years indicate pharmaceutical MSMEs operating in Kenya have seen a decline in profits and stagnation. The study therefore sought to establish the effect of digital transformation elements, including e-procurement, e-marketing, e-payment, and telemedicine, on the market performance of pharmaceutical Micro, Small, and Medium Enterprises (MSMEs) in Nairobi City County, Kenya. The research examines the limited understanding of how these digital technologies influence market performance, particularly in the pharmaceutical MSME sector. The study employs a cross-sectional descriptive research design, surveying 122 MSMEs from an initial target population of 175, selected through proportionate and simple random sampling. The questionnaire was tested for validity and reliability using Cronbach's alpha with a threshold of 0.7. Quantitative data were analyzed through multiple regression and correlation analysis to determine the strength of the relationships between variables. The results reveal that e-procurement, e-marketing, e-payment, and telemedicine significantly and positively affect market performance. The findings suggest that these digital strategies enhance procurement efficiency, marketing outreach, financial transactions, and healthcare service delivery, ultimately improving the market performance of pharmaceutical MSMEs.JEL Classification Codes: L86, M15, O33, L25.